Biomarcadores no infarto agudo do miocárdio com supradesnivelamento do segmento ST - Luiz Ricardo de Ataide Castro (2013)
Introduction: Biomarkers are commonly used in myocardial infarction with STsegment elevation (STEMI) and may be useful in assessing prognosis. This study evaluated the association between plasma levels of biomarkers IL-33, ST2, APN, BDNF and BNP and 30-day mortality in patients with STEMI and the association between plasma levels of these biomarkers among themselves and with the GRACE risk score, levels of troponin I and ejection fraction (LVEF). Methods: This was a cohort study which included 131 patients admitted consecutively who met the diagnostic criteria for STEMI. All patients underwent a standardized diagnostic approach, according to a clinical protocol, including serial ECG, echocardiogram, serum troponin I and, where appropriate, coronary angiography. Blood samples for measurement of biomarkers were obtained within the first 24 hours after admission to the coronary care unit and vital status was assessed with 30 days of the event. Results: Of the 131 patients, eight were excluded and 123 patients were divided into two groups: non-survivors - n = 11 (8.9%) - and survivors - n = 112 (91.1%). The mean age was 60 ± 12 years, with a predominance of males (n = 88, 72%). Seventy-three patients (59%) underwent reperfusion therapy during the acute phase (41 - thrombolysis, 26 - primary angioplasty and 6 - rescue angioplasty). The median time to reperfusion (between the onset of pain and initiation of fibrinolytic or the first balloon inflation in PPCI) was 292 minutes. Among the biomarkers measured in the first 24 hours of hospitalization, only the levels of IL-33 were significantly higher in patients who subsequently died compared to survivors (82.6 [59.7 to 392.7] vs 23, 1 [2.5-95.9], p = 0.003). Regarding the association between biomarkers, IL-33 and ST2 were correlated (rs = 0.256, p = 0.005) and ST2 correlated with peak troponin (rs = 0.430, p <0.001). BNP levels, IL-33 and ST2 correlated with other variables, such as LVEF. The analysis of the receiver operator characteristic curve (ROC) was used to identify variables that could predict 30-day mortality. Only the levels of IL-33 were statistically significant, with the area under the ROC curve of 0.756 (95% CI 0.640 to 0.871, p = 0.008). Conclusions: Elevated IL-33 was associated with 30-day mortality. Measurement of levels of IL-33 has potential for use in risk stratification of STEMI.